Identification of Potential Biomarkers for Liver Cancer Through Gene Mutation and Clinical Characteristics - Cui, Yunlong; Li, Hua; Zhan, Hongjie; Han, Tao; Dong, Yixuan; Tian, Caijuan; Guo, Yixian; Yan, Fang; Dai, Dong; Liu, Pengfei (Frontiers in Oncology, 2021)
Liver cancer is a common malignant tumor worldwide, which is a serious threat to the health of people. We try to investigate some mutations and clinical indicators as candidate markers for the development of liver cancer through targeted region capture technology combined with next-generation sequencing. We collected peripheral blood and liver cancer tissue samples from 32 liver patients concurrently. The SeqCap EZ Prime Choice Probes was used to perform the targeted enrichment, this probe captures 1000 known cancer-associated genes. We calculated the TMB for each patient. The high frequency mutations and these relative genes were identified. Eventually, survival analysis was performed based on the mutations and clinical indicators. In 32 liver patients, a total of 29 high frequency mutations were investigated. They were located in 25 genes, which were enriched in 9 CCs, 6 MFs and 21 BPs. Among them, EZH2 c.1544A>G and CCND1 c.839A>T had the highest mutation frequency (5/32). In the PPI network, EZH2-DNMT3A, NOTCH1-CCND1 and ABL1-CCND1 were the top 3 pairs. The survival analysis showed that there were significant differences in PFS and OS between the KPS groups.the PFS and OS in the TMB high group were higher than those in the TMB low group. OS and tumor stage had a remarkable relationship. In conclusion, EZH2 c.1544A>G and CCND1 c.839A>T might be potential biomarkers of liver cancer. TMB might be used as a prognosis and survival indicator of liver cancer.